learning counseling: learning counseling (Pedagogical Horizons, 2017)
One of the main responsibilities of teachers is to supervise their students in the process of learning. The idea of how this task is to be  attended to has changed over the past years. The perception of a teacher as a pure facilitator of knowledge is getting more and more out of focus. If students should be supported in their individual learning process as best as possible, the focus of the teacher should be in the role of a  (learning) advisor. The article in hand shows how learning counseling can be learned on the basis of a competence model and the experiences students get through that.
Keywords: learning counseling; counseling competence; new learning culture